Design and 3D printing of satellite structure components - Lim, Tong Zhen (2016)
3D printing is gaining popularity as a method of manufacture in various sectors, including the space industry. However, 3D printing for and in space is relatively new and there is a lack of material qualification processes available. This study looked into methods to qualify 3D printing materials for space applications. Two materials were used for this study, the ABSplusTM-P430 and ULTEMTM 9085. The latter is a space-approved material that is currently used. The former is used as a basis of comparison in this study. Additionally, the study looked into the effect of 3D printing on mechanical properties of the materials. Specifically, the effect of build orientation (i.e. the way 3D printing progresses layer-by-layer when building an object) on a fixed +45°/-45° raster angle was examined. Tension, compression, bending and fatigue tests were carried out with these materials following ASTM Standards closely. Fracture analyses were conducted, using visual inspection and Scanning Electron Microscopy. The mechanical tests showed that the build directions did affect tensile and flexural properties, but did not have a significant effect on the compressive strength. The fracture analyses showed that the samples failed differently based on the build directions. The microscopic images revealed different fracture patterns. The microscopic images of the fractures of the flexural tests highlighted different compressive and tensile characteristics. The fatigue tests showed that the examined build directions had no effect on the fatigue strength. The endurance limit of the ABSplusTM-P430 is approximately 10% of its ultimate tensile strength. In the tension and fatigue tests, dogbone-shaped specimens were used but they were found to be ineffective in transferring stress to the gauge region. As an alternative, rectangular specimens were tested. For future studies, alternative specimen shapes may be examined. A number of alternative specimens for compression tests are also suggested.